A more efficient current source inverter with series connected AC capacitors for photovoltaic and fuel cell applications - Klumpner, Christian; Chonlatee, Photong; Wheeler, Patrick (2008)
Renewable energy sources such as photovoltaics (PVs) or fuel cells (FCs) are not fitted for direct power grid connection because they deliver DC voltage and current. In addition, they also have a high internal resistance/nonlinear V/I dependence, which is why a power electronic interface is always needed. This paper presents the implementation of a three-phase power electronic interface for PV/FCs that uses a single conversion stage approach based on a current source inverter (CSI) topology with series connected capacitors, that would need only six reverse blocking IGBTs and due to the possibility to reduce the AC voltage at high load, would reduce the size of magnetics and the losses compared to a standard CSI.